Copiar el Eden : Arte reciente en Chile. - Mosquera, Gerardo; Berrios, Maria; Machuca, Guillermo; Maza, Josefina de la; Mellado, Justo Pastor; Mena, Catalina; Richard, Nelly; Valdés, Adriana; Valdés, Catalina (Santiago de Chile : Puro Chile Santiago Chile, 2006)
Adasme, Elias ; Altamirano, Carlos ; Apocalipsis, Yeguas del ; Arias, Carlos ; Atria, Magdalena ; Babarovic, Natalia ; Bengoa, Monica ; Benmayor, Samy ; Brugnoli, Francisco ; Cabieses, Jorge ; CADA ; Castillo, Juan ; Castillo, Victor ; Céspedes, Juan ; Cifuentes, Guillermo ; Correa, Claudio ; Corvalan, Maximo ; Diaz, Gonzalo ; Dittborn, Eugenio ; Donoso, Luz ; Downey, Juan ; Duclos, Arturo ; Eltit, Diamela ; Errázuriz, Paz ; Errazuriz, Virginia ; Ferrer, Pablo ; Fontecilla, Josefina ; Galeria Chilena ; Gatica, Omar ; Gelcich, Catalina ; Gonzalez, Nury ; Grupo Al Margen ; Guerra, Luis Enrique Silvestre ; Gumucio, Ignacio ; Hamilton, Patrick ; Hoffmann's House ; Jaar, Alfredo ; Jarpa, Voluspa ; Langlois Vicuña, Juan Pablo ; Langlois, Pablo ; Lehyt, Cristobal ; Leppe, Carlos ; Marin, Livia ; Maturana, Carlos ; Mezza, Gonzalo ; Moraga, Marcela ; Mujica, Felipe ; Navarro, Iván ; Navarro, Mario ; Oyarzun, Bernardo ; Parada, Hernan ; Parra, Cataline ; Prats, Fernando ; Preece, Sebastian ; Rivera, Pablo ; Rosenfeld, Lotty ; Ruff, Carolina ; Schopf, Demian ; Silva-Avaria, Cristian ; Smythe, Francisco ; Soro, Mario ; Steeger K., Patrick ; Tacla, Jorge ; Truffa + Cabezas ; Unzueta, Johanna ; Valdes, Francisco ; Vargas, Eugenia ; Velasco, Rosa ; Vicuña, Cecilia ; Villarreal, Alicia ; Yañez, Camilo ; Zamudio, Enrique ; Zomosa, Ximena ; Zurita, Raul
Bibliog. p. 633-645
Biog. auteurs P; 598-599
Geboorteplaats en -datum per kunstenaar
Engels
Spaans
boek
Keywords: Chili